Tingkat Kepuasan Pasien terhadap Pelayanan Obat dan Penanganan Rawat Inap bagi Pengguna BPJS Di Rumah Sakit Dunda Kabupaten Gorontalo - Hendrik David Julianus Borolla (Celebes Health Journal, 2020)
This study aims to determine the relationship between the level of patient satisfaction with drug services and the handling of inpatient care at the Dunda Hospital in Gorontalo District. The study sample was inpatients who used BPJS in Gorontalo District Dunda Hospital which were randomly taken as many as 30 people. The level of patient satisfaction was valued using a validated questionnaire. Patients who were used as respondents were part of patients who used inpatient services in hospitals. Gorontalo District Delegation and accepted and eligible to be used as respondents based on respondents' eligibility indicators. The method used in this study was an observational analytic method using a cross sectional design and data analysis was performed using descriptive analysis. The results showed that the level of patient satisfaction with drug service and inpatient care consisted of three categories of satisfaction, quite satisfied and dissatisfied. The results of the study showed that the facts of the patients were not related to the level of patient satisfaction with drug services and hospitalization at Dunda Hospital.